Consequences of clearing and tillage on the soil of a natural Amazonian ecosystem - Da, Paulo F.; Cerri, Carlos C.; Volkoff, Boris; Andreux, Francis G.; Chauvel, Armand (Forest Ecology and Management, 1991)
A comparative study was performed in the Oriental Amazon region of Brazil, on an experimental area of yellow latosol and red-yellow podzolic soils. Taking the forest soil as a reference, the chemical, physical, and micromorphological changes occurring after sequential burning, tillage and fallow-land were studied. Deforestation and tillage were responsible for a decreasing content and qualitative changes in organic matter; fulvic acid content first increased, then humic acid content decreased, giving rise to an increasing destruction of clay/organic complexes in the A horizon. As a result, a greater dispersion and migration of fine particles occurred, causing the obstruction of macropores and an increase in bulk density. Crop production decreased in two years, and the soil had to be abandoned. A secondary vegetation developed, and yielded organic residues which stimulated faunal activity. After three years under fallow, the above observed soil degradation processes were partially reversed. © 1991.
Keywords: Burning; Deforestation; Forest Clearance; Latosol; Organic Matter; Podzol; Rainforest Soil; Soil; Soil Particle Migration; Soil Transformation; Tillage; Brazil, Amazon; Brazil, Amazon Basin; South America, Amazonia